In vivo1H MRS of human gallbladder bile at 3 T in one and two dimensions: detection and quantification of major biliary lipids1. (14th August 2014) - Mohajeri, Sanaz; Ijare, Omkar B.; Bezabeh, Tedros; King, Scott B.; Thomas, M. Albert; Minuk, Gerald; Lipschitz, Jeremy; Kirkpatrick, Iain; Smith, Mike; Smith, Ian C. P.
<x xml:space="preserve">Abstract</x> In vitro 1H MRS of human bile has shown potential in the diagnosis of various hepatopancreatobiliary (HPB) diseases. Previously, in vivo1H MRS of human bile in gallbladder using a 1.5 T scanner demonstrated the possibility of quantification of choline‐containing phospholipids (chol‐PLs). However, other lipid components such as bile acids play an important role in the pathophysiology of the HPB system. We have employed a higher magnetic field strength (3 T), and a custom‐built receive array coil, to improve the quality of in vivo1H MRS of human bile in the gallbladder. We obtained significant improvement in the quality of 1D spectra (17 healthy volunteers) using a respiratory‐gated PRESS sequence with well distinguished signals for total bile acids (TBAs) plus cholesterol resonating at 0.66 ppm, taurine‐conjugated bile acids (TCBAs) at 3.08 ppm, chol‐PLs at 3.22 ppm, glycine‐conjugated bile acids (GCBAs) at 3.74 ppm, and the amide proton (−NH) arising from GCBAs and TCBAs in the region 7.76–8.05 ppm. The peak areas of these signals were measured by deconvolution, and subsequently the molar concentrations of metabolites were estimated with good accuracy, except for that of TBAs plus cholesterol. The concentration of TBAs plus cholesterol was overestimated in some cases, which could be due to lipid contamination. In addition, we report the first 2D L‐COSY spectra of human gallbladder bile in vivo (obtained in 15 healthy volunteers). 2D L‐COSY spectra will be helpful in differentiating various biliary chol‐PLs in pathological conditions of the HPB system. Copyright © 2014 John Wiley & Sons, Ltd.